The Export Potential of Mining Commodities of Indonesia - Tui, Rini Novrianti Sutardjo; Anas, Aryanti Virtanti; Amalia, Rizki; Adachi, Tsuyoshi (EPI International Journal of Engineering, 2022)
The implementation of the export ban of the raw mineral commodities is one of the implications brought by the Mining Law Number 3 of the year 2020. The high contribution of the raw mining commodities towards the economy of Indonesia plays dual sides of a coin. First, it is seemingly more beneficial to increase the value of the raw commodities by processing and refining them first domestically. Then, as the raw commodities contribute largely, banning the export surely will bring a change towards the economy. Change in government’s regime initiate the review of the export ban. This research utilizes Herfindahl Hirschman Index and Revealed Comparative Advantage (RCA) to investigate how export ban can affect the economy growth. In analyzing the impact of the export ban, the very basic foundation is examining the export potential of the mining commodities. Analyzing the ores, metals, and minerals as export commodities, the ores and minerals seemingly are the prominent export commodities. Proved by the RCA index value, the government of Indonesia has a strong foundation to release the export ban. Additionally, the HH Index of market concentration indicates that the export trade of Indonesia is relatively independent towards its trading partner. Therefore, as the government of Indonesia sets to implement the export ban policy, this change in trade barriers is unlikely will disrupt the trade relations between Indonesia and its trading partners.